1999
DOI: 10.1097/00006454-199906000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum antibiotics and early onset neonatal sepsis caused by group B Streptococcus and by other organisms in Australia

Abstract: A steady fall in EOGBS infections in Australia from 1991 to 1997 has been associated with increasing use of intrapartum antibiotics. Increased antibiotic use is probably causal in the fall in GBS, because the incidence of early onset infections caused by other organisms has also fallen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
3
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 11 publications
3
92
3
4
Order By: Relevance
“…16 A review of 11 471 blood samples from all developing nations of the world revealed that Gram-negative rods were isolated in 60% of positive cultures, 15 with Klebsiella pneumoniae being the commonest organism. The national neonatal perinatal database for the year 2002-2003 from India has also shown Klebsiella pneumoniae as being the major pathogen (27-32%) in both intramural and extramural neonates.…”
Section: Discussionmentioning
confidence: 99%
“…16 A review of 11 471 blood samples from all developing nations of the world revealed that Gram-negative rods were isolated in 60% of positive cultures, 15 with Klebsiella pneumoniae being the commonest organism. The national neonatal perinatal database for the year 2002-2003 from India has also shown Klebsiella pneumoniae as being the major pathogen (27-32%) in both intramural and extramural neonates.…”
Section: Discussionmentioning
confidence: 99%
“…5,40,41 A comparable decline in early-onset disease following screening has been seen in Australia. 6,7 Potential harm from intrapartum penicillin prophylaxis Three possible hazards from intrapartum penicillin prophylaxis have been claimed.…”
Section: Microbiological Screeningmentioning
confidence: 99%
“…Early-onset neonatal GBS infection (though not late-onset) can be prevented by screening to identify high-risk pregnancies and administering penicillin during delivery (intrapartum 5 ), but there is a striking difference in policy in this respect between the USA and the UK. In the USA, screening in pregnancy is recommended by specialist medical organizations and is widely practiced 5 (this is also the case in Australia 6,7 ). In the UK, and in many European countries, screening is not recommended 8 or practiced, 9 and only scanty risk factor based screening is performed.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11] By comparison, rates reported in the United States and Australasia range from 1.5 to 3.5 per 1000 for EOS sepsis and up to 6 per 1000 live births for LOS sepsis, a total of 6-9 per 1000 for neonatal sepsis, and 0.3-3 per 1000 live births in Europe. [12][13][14][15][16] A number of organisms are associated with neonatal sepsis such as Klebsiella pneumoniae, Staphylococcus aureus, Group B Streptococcus (GBS), Escherichia coli, Pseudomonas aeruginosa, Acinetobacter spp and Enterobacter spp etc. 17 Gram-negative bacteria remain to be the major cause of neonatal sepsis in developing countries.…”
Section: Introductionmentioning
confidence: 99%